Band gap control and transformation of monolayer-MoS2-based hetero-bilayers1. Issue 36 (28th September 2015) - Li, X. D.; Wu, S. Q.; Zhu, Z. Z.
<x xml:space="preserve">Abstract</x> Tunable band gaps of MoS2-based hetero-bilayers can be realized by changing the interlayer spacing or employing in-plane compressing/stretching.